Shear wave liver elastography - Barr, Richard G. (Abdominal imaging, 2018)
Chronic liver disease is a substantial world-wide problem. Its major consequence is increasing deposition of fibrous tissue within the liver leading to the development of cirrhosis with its consequences of portal hypertension, hepatic insufficiency, and hepatocellular carcinoma. The stage of liver fibrosis is important to determine prognosis, surveillance, prioritize for treatment, and potential for reversibility. The process of fibrosis is dynamic and regression of fibrosis is possible with treatment of the underlying conditions. Previously, the only method of staging the degree of fibrosis was liver biopsy. The recent development of ultrasound elastography techniques allows a non-invasive method of estimating the degree of liver fibrosis. Transient elastography (TE) is a non-imaging elastographic technique, while point shear wave (p-SWE) and 2D-SWE combine imaging with elastography. The evidence at this time suggests that p-SWE is as accurate as but more reliable than TE, while 2D-SWE is more accurate than TE. This review discusses the background of chronic liver disease, the types of ultrasound elastography, how to perform an examination, and how to interpret the results.